Optimalisasi Proses Pemesanan Jasa Servis Komputer dan Laptop melalui Aplikasi Web Menggunakan Framework Codeigniter - Faris; Hartono; Pambudi, Randi Estian (LPPM Universitas Muhammadiyah Kotabumi, 2024)
The rapid growth of technology has made computers and laptops indispensable in various fields such as government, education, and commerce. Despite widespread ownership, users often lack the skills to handle technical issues, creating a demand for repair services. Many repair shops still rely on manual tools like Microsoft Word and Excel for operational tasks, which becomes inefficient as customer numbers grow. This research focuses on the development of a web-based service management system to address these challenges and enhance efficiency. Using the waterfall methodology, a systematic and sequential approach was employed to design and implement the system. The CodeIgniter framework, known for its PHP development efficiency and ease of implementation, was utilized. The system features include repair status tracking, customer account management, financial reporting, service order processing, and detailed payment tracking. These functionalities aim to improve the customer experience, increase operational efficiency, and simplify business processes.